Lessons learned from applying established cut-off values of questionnaires to detect somatic symptom disorders in primary care: a cross-sectional study - von Schrottenberg, Victoria; Toussaint, Anne; Hapfelmeier, Alexander; Teusen, Clara; Riedl, Bernhard; Henningsen, Peter; Gensichen, Jochen; Schneider, Antonius; Linde, Klaus; Dreischulte, Tobias; Falkai, Peter; Gensichen, Jochen; et al. (Frontiers in Psychiatry, 2024)
Introduction Based on two diagnostic accuracy studies in high-prevalence settings, two distinctly different combinations of cut-off values have been recommended to identify persons at risk for somatic symptom disorder (SSD) with the combination of the Patient-Health Questionnaire-15 (PHQ-15) and the Somatic Symptom Disorder—B Criteria Scale (SSD-12). We investigated whether the reported sensitivity and specificity of both recommended cut-off combinations are transferable to primary care. Methods In a cross-sectional study, 420 unselected adult primary care patients completed PHQ-15 and SSD-12. Patients scoring ≥9 and ≥ 23 (recommended cut-off combination #1) or ≥ 8 and ≥ 13 (recommended cut-off combination #2) were considered test-positive for SSD, respectively. To assess the validity of the reported sensitivity and specificity in different low- to high-prevalence settings, we compared correspondingly expected proportions of test positives to the proportion observed in our sample. Results Based on combination #1, 38 participants (9%) were found to be test positive, far fewer than expected, based on the reported values for sensitivity and specificity (expected minimum frequency 30% with a true prevalence ≥1%). This can only be explained by a lower sensitivity and higher specificity in primary care. For combination #2, 98 participants (23%) were test positive, a finding consistent with a true prevalence of SSD of 15% or lower. Discussion Our analyzes strongly suggest that the sensitivity and specificity estimates reported for combination #1 are not applicable to unselected primary care patients and that the cut-off for the SSD (≥23) is too strict. Cut-off combination #2 seems more applicable but still needs to be tested in studies that compare screening findings by questionnaires with validated diagnostic interviews as reference standards in primary care populations.